2017
DOI: 10.1590/1980-5497201700020003
|View full text |Cite
|
Sign up to set email alerts
|

Manifestações emocionais e motoras de ribeirinhos expostos ao mercúrio na Amazônia

Abstract: Introduction:The investigation of clinical and neurological impactations associated with exposure to mercury levels in exposed populations is necessary in the Amazon. Objective: To analyze emotional and motor symptoms of riverside dwellers exposed by diet in the municipalities of Itaituba and Acará, in Pará, Brazil. Methods: Hair samples were collected to assess the total mercury (HgT). Demographic data as well as emotional (depression, anxiety and insomnia) and motor (paresthesia, muscle weakness, loss of bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Recent studies regarding the effect of mercury on adult's health revealed emotional changes, such as depression and aggressiveness, motor problems [59], and changes in the visual field [60]. Furthermore, some studies have demonstrated an association between MeHg exposure with the development of neurodegenerative diseases such as Alzheimer's and Parkinson's disease [61,62].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies regarding the effect of mercury on adult's health revealed emotional changes, such as depression and aggressiveness, motor problems [59], and changes in the visual field [60]. Furthermore, some studies have demonstrated an association between MeHg exposure with the development of neurodegenerative diseases such as Alzheimer's and Parkinson's disease [61,62].…”
Section: Introductionmentioning
confidence: 99%
“…Riverine communities in the Amazon can consume between 100g and 550g of sh protein per capita per day 38 . Among recent studies in areas downstream of gold mining sites, hair total Hg concentrations ranged from 7.05-17.9 𝛍g/g in adults 35,[39][40][41][42][43][44] and 2.05-4.5 𝛍g/g in children [45][46][47] , well above the expected reference values of less than 1 𝛍g/g.…”
Section: Discussionmentioning
confidence: 93%
“…Chronically exposed Amazonian populations have demonstrated signi cant neuropathological ndings associated with mercury exposure, particularly cognitive 48,49 , vision 40,[50][51][52] , motor 42,48,49,53 , somatosensory 48,50,54 , and emotional de cits 42 . Speci cally in pediatric populations, mercury poisoning is associated with neurodevelopmental and motor de cits, including delayed milestone achievements, language problems, and low mental and psychomotor scores 46,47,55 .…”
Section: Discussionmentioning
confidence: 99%
“…The cohort studies conducted in the Faroe Islands and New Zealand indicate that even in low doses, the consumption of mercury-contaminated fish during pregnancy can cause important cognitive alterations in children [48,49]. The mercury neurotoxic potential effects in children and adults of the Amazon have been reported in recent publications [50][51][52][53][54]. The most common effects in children are cognitive problems, neurodevelopmental impairment, and psychomotor disorders.…”
Section: Discussionmentioning
confidence: 99%